Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1111/j.1439-0507.2008.01630.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, biochemical and molecular characterisation of the first Italian Candida africana isolate

Abstract: One atypical isolate of the pathogenic yeast Candida albicans was isolated from an Italian patient with vulvovaginitis. The strain, germ tube positive and chlamydospore-negative showed white-thin turquoise colonies on Candida ID 2 medium. The yeast was identified as Candida africana by using morphological and biochemical tests. On the basis of the molecular results obtained in this study as well as in other studies, C. africana cannot be yet considered as a new species of Candida. It is possible that C. africa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
27
1
5

Year Published

2009
2009
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 12 publications
9
27
1
5
Order By: Relevance
“…Moreover, Al-Hedaithy and Fotedar (1) recovered and studied 25 atypical C. albicans strains from 21 specimens from female patients in Saudi Arabia. The majority of these clinical isolates showed a carbohydrate assimilation profile typical of the C. africana strains reported in other studies (2,17).…”
supporting
confidence: 60%
“…Moreover, Al-Hedaithy and Fotedar (1) recovered and studied 25 atypical C. albicans strains from 21 specimens from female patients in Saudi Arabia. The majority of these clinical isolates showed a carbohydrate assimilation profile typical of the C. africana strains reported in other studies (2,17).…”
supporting
confidence: 60%
“…Furthermore, with the advent of molecular phylogenetic analysis, there have been several new species suggested as subdivisions of traditional species. For example, a recent study has suggested that the species Candida africana may be a separate species from C. albicans (41), but there is still uncertainty about this distinction (1,37). Similarly, recent work has shown that Candida parapsilosis groups II and III are actually separate species, Candida orthopsilosis and Candida metapsilosis, respectively (40), and that Cryptococcus neoformans has been described to have variants (25).…”
Section: Discussionmentioning
confidence: 99%
“…africana) (20), the taxonomic status of C. africana remains controversial. Although they are germ tube positive like C. albicans and C. dubliniensis, C. africana isolates studied to date have reportedly grown and produced hyphae more slowly than either C. albicans or C. dubliniensis and could be distinguished from both by an inability to assimilate several sugars or to produce chlamydospores and by appearance on chromogenic agars (18,19,(21)(22)(23). Moreover, despite an almost worldwide distribution, the overwhelming majority of C. africana isolates have been recovered from female genital specimens (reviewed in reference 16).…”
Section: T He Incidence Of Invasive Fungal Infections Caused By Unusualmentioning
confidence: 99%